2018
DOI: 10.1149/2.0321810jes
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—The Effectiveness of Multifunctional Li-Ion Battery Separators past Their Saturation with Transition Metal Ions

Abstract: Li-ion batteries (LIBs) for electric vehicles necessitate a 10-year useful life. The dissolution of manganese and other transition metal ions from positive electrodes, and the loss of Li + ions are two main causes for reduced LIB durability. Multifunctional separators (MFSs) designed to mitigate these degradation modes enable improvements in the electrochemical performance of LIBs at both room and above-ambient temperatures. We report herein on the benefits for the cycle life and rate performance of Li x Mn 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…There are two main reasons for investigating a variety of TM trapping materials. First, our data clearly show that Mn 3+ and not Mn 2+ is the dominant Mn cation in the electrolyte solutions from LMO//graphite 26,[60][61][62][63][64][65][66][67][68] (see Figure 2) as well as LNMO//graphite cells, 69 also that the Mn 2+ to Mn 3+ ratio is different in cells with LMO than in cells with LNMO. 69 Furthermore, the trapping capacities for various transition metal ions vary from material to material.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…There are two main reasons for investigating a variety of TM trapping materials. First, our data clearly show that Mn 3+ and not Mn 2+ is the dominant Mn cation in the electrolyte solutions from LMO//graphite 26,[60][61][62][63][64][65][66][67][68] (see Figure 2) as well as LNMO//graphite cells, 69 also that the Mn 2+ to Mn 3+ ratio is different in cells with LMO than in cells with LNMO. 69 Furthermore, the trapping capacities for various transition metal ions vary from material to material.…”
mentioning
confidence: 72%
“…After having shown that separators functionalized with various TM trapping materials can prevent the deposition of Mn cations dissolved from LMO onto graphite during cycling at both room and above-ambient temperatures, [65][66][67] we focused recently on demonstrating that the chemically active separators concept may have practical relevance. Specifically, we showed that improvements in cycle life is still obtained with functional separators having realistic dimensions (10 to 25 μm thickness), 63 that the saturation of the functional separators with TM ions does not affect the retention capacity during high-temperature cycling 63,64 and that, in addition, functionalized separators can also improve rate performance. 63 We also investigated the microscopic underpinning of the observed improvements in electrochemical performance.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In the early stage of batteries operation with low HF content and the formation of passivation surface films, the acid-removing capability of the acid-scavenging separator is far from saturation, which can effectively remove acid substances and promote the formation of uniform and compact passivation film. Thereby it significantly improves the cycling performance of the battery, even with the generation of H 2 O in subsequent stages, which is similarly argued for in the study of Shilina et al and Banerjee et al 50,112 However, this effect may make a significant difference on the battery performance due to the variation of initial water (acid) content in the battery, which needs further in-depth exploration. Even for separators using ceramic oxide nanoparticles as acid removal materials, the hazardous species it clears may not be the HF in the electrolyte, but the H 2 O molecules.…”
Section: Further Development and Challenges Of Acid-scavenging Membranesmentioning
confidence: 71%
“…The inclusion of different fillers into a PVDF matrix proved to increase the ionic conductivity of the membrane, its thermal and mechanical stability, as well as the rate performance of the batteries. Al2O3 [50], Poly(IDANa2) [51], SnO2 [52],…”
Section: Solvent Castingmentioning
confidence: 99%